Sandwich EVAR occludes Celiac and Superior Mesenteric Artery for Infected Suprarenal Abdominal Aortic Aneurysm Treatment. (10th May 2018) - Prasertcharoensuk, Supatcha; Wongkonkitsin, Narongchai; Tunmit, Parichat; Theeragul, Su-a-pa; Ahooja, Anucha
Abstract : Introduction . Infected aortoiliac aneurysms are rare, representing only 1% to 2% of all aortic aneurysms; we present a case of infected suprarenal aortic aneurysm with a nearly occluded celiac artery and superior mesenteric artery treated using an endovascular technique to preserve collateral in the retroperitoneal space from the inferior mesenteric artery for supplying visceral organs.